Catalyst for preparing acrolein as well as preparation method and application of catalyst
By adding molybdenum-bismuth-based composite oxides, metal oxides and nanostructure accelerators to the catalyst, the composite catalyst is formed, which solves the problems of insufficient activity, selectivity and stability of the existing catalysts, and achieves a higher propylene conversion rate and acrolein selectivity, extends the service life of the catalyst and reduces production costs.
Patent Information
- Application Number
- CN202411613811.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
AI Technical Summary
In the process of oxidation of propylene, the activity, selectivity and stability of existing catalysts still need to be improved in terms of activity, selectivity and stability, which is difficult to meet the needs of industrial production.
Molybdenum-bismuth-based composite oxide is used as the main body of the catalyst, and specific metal oxides and nanostructure accelerators are added to form a composite catalyst. The catalyst improves the activity and selectivity of the catalyst by optimizing the pore size distribution, enhancing mechanical strength and thermal conductivity.
It improves the propylene conversion rate and acrolein selectivity, extends the service life of the catalyst, reduces production costs, and improves the purity of the product.
Smart Images

Figure BDA0005131606920000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and more specifically, to a catalyst for preparing acrolein and a preparation method and application thereof. Background Art
[0002] Acrolein is the simplest unsaturated aldehyde and an important chemical synthesis intermediate. Its largest application area is the synthesis of methionine and acrylic acid. It is also widely used in the synthesis of important chemical products such as methylpyridine, pyridine, glutaraldehyde and acrylic acid. It can also be used as an important raw material for the synthesis of 1,3-propylene glycol. Acrolein has active chemical properties and a complex synthesis process. There are not many domestic manufacturers. It is mainly used as an intermediate product in the production of acrylic acid.
[0003] Acrolein was first produced by gas phase condensation of formaldehyde and acetaldehyde, and was industrialized in 1942. The catalyst at that time was silica gel impregnated with sodium silicate. Since then, countries have continued to use this process route until the industrialization of propylene oxidation. Currently, propylene oxidation is widely used in industry to produce acrolein, accounting for more than 80%. Propylene can be selectively oxidized to produce acrolein using propylene as a raw material, or acrolein can be further oxidized to produce acrylic acid using acrolein as an intermediate product.
[0004] Propylene oxidation to acrolein is a highly exothermic, internal diffusion-controlled reaction. In addition to good intrinsic properties, the catalyst used must also have good physical properties, such as pore size distribution, specific surface area, etc. It should have thermal shock resistance and mechanical strength to meet the requirements of fixed bed reactors. Traditional catalysts are mainly based on Mo-Bi as the main system, and some co-catalysts with surface alkalinity are added to improve the catalyst selectivity. However, the existing catalysts still need to be improved in terms of activity, selectivity and stability.
[0005] Therefore, a catalyst for preparing acrolein and a preparation method and application thereof are now proposed. Summary of the invention
[0006] In order to overcome the above defects of the prior art, the present invention provides a catalyst for preparing acrolein and a preparation method and application thereof, so as to solve the problems raised in the above background technology.
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a catalyst for preparing acrolein, comprising a molybdenum-bismuth composite oxide, a metal oxide and a nanostructure promoter, wherein the metal oxide is selected from at least one of TiO2, NiO, ZnO, La2O3, CeO2, CuO, Ga2O3, MgO and SnO2 and has a crystal structure; the nanostructure promoter is a nanoparticle with a specific morphology, selected from at least one of carbon nanotubes and graphene, and is uniformly dispersed in the catalyst at a mass ratio of 0.1 to 5%, so as to enhance the mechanical strength and thermal conductivity of the catalyst.
[0008] Preferably, the crystal structure of the metal oxide is needle-shaped or flake-shaped, wherein the diameter of the needle-shaped metal oxide is 5 to 150 nm and the length is 0.1 to 50 μm; the length of the flake-shaped metal oxide is 20 to 200 nm and the width is 15 to 80 nm; and the crystal specific surface area of the metal oxide is 50 to 150 m 2 / g to further optimize the activity and selectivity of the catalyst.
[0009] Preferably, the molybdenum-bismuth composite oxide has a general formula as shown in formula (I):
[0010] Mo 12 Bi a Fe b Co c Ni d A e B f C' g D h O n (I);
[0011] Wherein: Mo, Bi, Fe, Co, Ni represent molybdenum, bismuth, iron, cobalt and nickel respectively, A is selected from at least one element of alkali metals and alkaline earth metals, B is selected from at least one element of chromium, tin, zinc, antimony and phosphorus, C' is selected from at least one element different from C of silicon, zirconium and aluminum to introduce additional active sites, D is the element represented by the nanostructure promoter (in the form of oxide), O is oxygen; a, b, c, d, e, f, g, h and n represent the atomic ratio of Bi, Fe, Co, Ni, A, B, C', D and O respectively; 1<a≤4, 1.5<b≤5, 1<c≤6, 0.05<d≤7, 0.05<e≤2.5, 0.02≤f≤4, 0.5<g≤15, 0.001<h≤0.05, n is a value determined according to the oxidation state of each element.
[0012] A method for preparing a catalyst, for preparing the catalyst for preparing acrolein according to claim 3, comprising the following steps:
[0013] a) preparing an active ingredient solution of a molybdenum-bismuth composite oxide;
[0014] b) mixing a metal oxide precursor solution with an active ingredient solution to form a suspension;
[0015] c) adding a dispersion of a nanostructure promoter to the suspension, and achieving uniform dispersion by ultrasonic treatment or high-speed stirring;
[0016] d) drying, shaping and calcining the mixture obtained in step c) to obtain the catalyst.
[0017] An application of a catalyst, an application of a catalyst prepared according to the above-mentioned method for preparing a catalyst, wherein the catalyst is used for selective oxidation of propylene to produce acrolein in the presence of molecular oxygen or a condition containing molecular oxygen.
[0018] Preferably, the oxidation reaction is carried out under optimized reaction conditions, including a reaction tube inner diameter of 20 to 30 mm, a reaction tube length of 3000 to 5000 mm, a catalyst loading height of 2500 to 4000 mm, and a total material space velocity of 800 to 2400 h -1 , in order to further improve the selectivity and yield of acrolein.
[0019] The catalyst for preparing acrolein provided by the present invention, and its preparation method and application have the following beneficial effects:
[0020] The acrolein catalyst disclosed in the present invention has an optimized pore size distribution, wherein the pore volume with a pore size of less than 50 nm accounts for 35-50% of the total pore volume; the pore volume with a pore size of 50 to 100 nm accounts for 30-45% of the total pore volume; and the pore volume with a pore size of greater than 100 nm accounts for 20-30% of the total pore volume. This unique pore size distribution enables the catalyst to have a higher propylene conversion rate and improves production efficiency;
[0021] The catalyst of the present invention has a sophisticated preparation process, such as optimization of low-temperature nitrogen adsorption-desorption curve, control of programmed temperature reduction curve, etc., so that the catalyst exhibits higher stability during the reaction process, prolongs the service life of the catalyst, and reduces production costs;
[0022] By adding a specific co-catalyst to the Mo-Bi system and strictly controlling the molar ratio of each element, the catalyst of the present invention exhibits higher selectivity in the reaction of propylene oxidation to produce acrolein, reduces the amount of byproduct acrylic acid generated, and improves the purity of the product;
[0023] The catalyst preparation process of the present invention avoids adding binders, pore-forming agents, etc., but relies on the viscosity of the catalyst matrix itself to form, and strictly controls the ratio and forming pressure between the precursors, so that the pore structure of the catalyst is finalized, and at the same time improves the mechanical strength of the catalyst, so that it is not easy to pulverize during use, ensuring that the catalyst exhibits high conversion rate and high selectivity at high space velocity and performs stably for a long time. DETAILED DESCRIPTION
[0024] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0025] In the examples given below, the definitions of acrolein conversion, acrylic acid yield and selectivity, drop impact strength, and pulverization degree are as follows:
[0026] Acrolein conversion rate (%) = (number of moles of acrolein reacted / number of moles of acrolein in the raw material) × 100%
[0027] Acrylic acid yield (%) = (mol number of acrylic acid produced / mole number of acrolein in the raw material) × 100%
[0028] Selectivity of acrylic acid (%) = (mol number of acrylic acid produced / mol number of acrolein reacted) × 100%
[0029] Mechanical strength (%) = (mass of catalyst remaining on the sieve / mass of catalyst falling) × 100
[0030] Degree of pulverization (%) = (mass of catalyst - mass of catalyst remaining on the sieve) / mass of catalyst × 100
[0031] The present invention will be further described below by way of examples.
[0032] Example 1
[0033] This embodiment provides a catalyst for preparing acrolein, and the preparation method thereof comprises the following steps:
[0034] Preparation of molybdenum-bismuth composite oxide precursor: 800.0g ammonium molybdate, 60g magnesium nitrate, 329.7g bismuth nitrate, 686.5g iron nitrate, 306.6g cobalt nitrate, 570.9g nickel nitrate, 215.5g zinc nitrate were dissolved in distilled water to form a mixed solution. The solution was heated and stirred vigorously to allow the components to react fully. Then 159.8g silicon oxide was added and stirred to make it evenly dispersed.
[0035] Add metal oxides: Add an appropriate amount of needle-shaped TiO2 powder (diameter 10 nm, length 1 μm, crystal specific surface area 100 m2 / g) and stir evenly.
[0036] Adding nanostructure promoter: Evenly dispersing an appropriate amount of graphene nanosheets (at a mass ratio of 0.5%) in the above solution to enhance the mechanical strength and thermal conductivity of the catalyst.
[0037] Drying and calcining: The suspension is dried to a solid state, and then calcined at 540°C to obtain active powder of the catalyst. The active powder is molded to obtain the desired catalyst particles.
[0038] Example 2
[0039] The catalyst preparation method of this embodiment is similar to that of embodiment 1, except that:
[0040] The metal oxide is selected as ZnO with a flake structure (length 50nm, width 30nm, crystal specific surface area 80m 2 / g).
[0041] The nanostructured promoter is nano-alumina fiber, and the added amount is 2% of the total mass of the catalyst.
[0042] Example 3
[0043] The catalyst preparation method of this embodiment is similar to that of embodiment 1, except that:
[0044] The metal oxide is a mixture of NiO and CuO (both have needle-like structures, with a diameter of 20 nm and a length of 0.5 μm for NiO and a diameter of 15 nm and a length of 1 μm for CuO; the crystal specific surface area of both is 120 m 2 / g), the addition ratio is 1:1.
[0045] The nanostructured promoter is carbon nanotubes, and the added amount is 1% of the total mass of the catalyst.
[0046] Comparative Example 1
[0047] This comparative example provides a catalyst for preparing acrolein, and the preparation method thereof is similar to that of Example 1, but the addition of the nanostructured promoter is omitted.
[0048] Comparative Example 2
[0049] This comparative example provides a catalyst for preparing acrolein. The preparation method is similar to that of Example 1, but the metal oxide is selected to be ordinary ZnO powder without a crystal structure.
[0050] Comparative Example 3
[0051] This comparative example provides a catalyst for preparing acrolein. The preparation method is similar to that of Example 1, but the nanoparticles selected as the nanostructured promoter are nano-gold spheres.
[0052] Experimental Example 1 Catalyst Mechanical Strength Test
[0053] 100 g of catalyst was placed on the top of a vertically erected stainless steel tube with a length of 3.5 m and an inner diameter of 25.4 mm. The tube was loosened and allowed to fall freely onto a 2 mm thick stainless steel plate at the bottom of the tube. The fallen catalyst was sieved with a 20-mesh sample sieve, and the mass of the catalyst remaining on the sample sieve was measured. The mechanical strength of the catalyst was calculated. The results are listed in Table 1.
[0054] Experimental Example 2 Catalytic Performance Test
[0055] In a fixed bed reactor with an inner diameter of 25.4 mm and a tube length of 4000 mm, 1.4 to 1.7 L of catalyst or a diluted catalyst mixed with inert porcelain balls is loaded, and propylene, oxygen, nitrogen and water vapor are introduced therein, wherein the molar concentration of propylene is 7.5 to 10%, propylene: air: nitrogen: water vapor = (7.5 to 10): (70 to 80): (16 to 20): (6.5 to 15). The total material space velocity is 2300 h -1 The oxidation reaction was carried out at a reaction temperature of 315-350°C and a pressure of 50 kPa. The results after the reaction was carried out for 800 hours are listed in Table 1.
[0056] Table 1 Evaluation results of embodiments and comparative examples
[0057]
[0058] shape)+Nano-gold spheres (non-specified shape)
[0060] It can be seen from Table 1 above that the performance of the catalysts of Examples 1-3 of the present invention is significantly better than that of the catalysts of Comparative Examples 1-3.
[0061] Specifically, from the perspective of mechanical strength:
[0062] The catalysts in all the examples showed relatively high mechanical strength, all above 98.2%, which may be due to the fact that the addition of the nanostructured promoter enhanced the mechanical properties of the catalyst.
[0063] The mechanical strength of the catalysts in the comparative examples is relatively low, especially the comparative example 1 in which the nanostructured promoter is omitted, whose mechanical strength is 95.0%, indicating that the nanostructured promoter has a significant effect on improving the mechanical strength of the catalyst.
[0064] From the conversion rate of propylene:
[0065] The catalysts in all the examples and comparative examples showed high propylene conversion rates, all above 97.5%, which indicates that the molybdenum-bismuth composite oxide as the catalyst main body has high activity for the conversion of propylene.
[0066] However, the conversion rates of the catalysts in the examples are generally slightly higher than those in the comparative examples, especially in Example 3, which has a conversion rate of 99.2%, the highest among all the catalysts, which may be related to its specific combination of metal oxides and nanostructured promoters.
[0067] From the yield of acrolein:
[0068] The acrolein yield of the catalysts in the examples is above 87.0%, which is significantly higher than that of the catalysts in the comparative examples. This indicates that the crystal structure of the metal oxide and the addition of the nanostructured promoter have an important influence on increasing the acrolein yield.
[0069] The acrolein yield of the catalysts in the comparative examples is relatively low, especially when the metal oxide is ordinary ZnO powder without a crystalline structure (Comparative Example 2), the yield is 84.5%, the lowest among all the catalysts.
[0070] From the selectivity of acrolein:
[0071] The acrolein selectivity of the catalysts in the examples is all above 88.0%, indicating that these catalysts have high selectivity in the process of catalyzing the conversion of propylene into acrolein.
[0072] The selectivity of the catalyst in the comparative example is relatively low, especially when the nanostructured promoter is omitted or the metal oxide is amorphous, the selectivity decreases more significantly. This indicates that the nanostructured promoter and the crystal structure of the metal oxide play an important role in improving the selectivity of acrolein.
[0073] In summary, the catalysts in the examples all showed better performance than the comparative examples in terms of mechanical strength, propylene conversion, acrolein yield and selectivity, which was mainly due to the crystal structure of the metal oxide, the addition of the nanostructured promoter and the synergistic effect between them.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A catalyst for preparing acrolein, characterized in that The invention comprises a molybdenum-bismuth composite oxide, a metal oxide and a nanostructure promoter, wherein the metal oxide is selected from at least one of TiO2, NiO, ZnO, La2O3, CeO2, CuO, Ga2O3, MgO and SnO2 and has a crystal structure; The nanostructure promoter is a nanoparticle with a specific morphology, selected from at least one of carbon nanotubes and graphene, and is uniformly dispersed in the catalyst at a mass ratio of 0.1 to 5%.
2. A catalyst for preparing acrolein according to claim 1, characterized in that: The crystal structure of the metal oxide is needle-shaped or flake-shaped, wherein the diameter of the needle-shaped metal oxide is 5 to 150 nm and the length is 0.1 to 50 μm; the length of the flake metal oxide is 20 to 200 nm and the width is 15 to 80 nm; and the crystal specific surface area of the metal oxide is 50 to 150 m 2 / g.
3. A catalyst for preparing acrolein according to claim 2, characterized in that: The molybdenum-bismuth composite oxide has a general formula as shown in formula (I): Mo 12 Bi a Feb b Co c Ni d A e B f C' g D h O n (Ⅰ); Wherein: Mo, Bi, Fe, Co, Ni represent molybdenum, bismuth, iron, cobalt and nickel respectively, A is selected from at least one element of alkali metals and alkaline earth metals, B is selected from at least one element of chromium, tin, zinc, antimony and phosphorus, C' is selected from at least one element different from C of silicon, zirconium and aluminum to introduce additional active sites, D is the element represented by the nanostructure promoter (in the form of oxide), O is oxygen; a, b, c, d, e, f, g, h and n represent the atomic ratio of Bi, Fe, Co, Ni, A, B, C', D and O respectively; 1<a≤4, 1.5<b≤5, 1<c≤6, 0.05<d≤7, 0.05<e≤2.5, 0.02≤f≤4, 0.5<g≤15, 0.001<h≤0.05, n is a value determined according to the oxidation state of each element.
4. A method for preparing a catalyst, for preparing the catalyst for preparing acrolein according to claim 3, characterized in that: The following steps are involved: a) preparing an active ingredient slurry of a molybdenum-bismuth composite oxide; b) mixing a metal oxide precursor solution with an active ingredient slurry to form a suspension; c) adding a dispersion of a nanostructure promoter to the suspension, and achieving uniform dispersion by ultrasonic treatment or high-speed stirring; d) drying, shaping and calcining the mixture obtained in step c) at a calcination temperature of 450-600° C. to obtain the catalyst.
5. An application of a catalyst, the application of a catalyst prepared by the method for preparing a catalyst according to claim 4, characterized in that: The catalyst is used for selective oxidation of propylene to produce acrolein in the presence of molecular oxygen or a condition containing molecular oxygen.
6. The use of a catalyst according to claim 5, characterized in that: The oxidation reaction is carried out under optimized reaction conditions, including a reaction tube inner diameter of 20 to 30 mm, a reaction tube length of 3000 to 5000 mm, a catalyst loading height of 2500 to 4000 mm, and a total material space velocity of 800 to 2400 h -1 .